Intelligence: Past present and future - Raman, B (New Delhi, 2002)
This book is invaluable not merely for those engaged in intelligence gathering and dissemination but also for every student of current affairs and indeed everyone who wishes to remain abreast of the current international political and military scenario.
Keywords: Military Intelligence